An Optimized Miniaturized Ultrasound Transducer for Transcranial Neuromodulation - Hou, Chenxue; Wu, Yan; Fei, Chunlong; Qiu, Zhihai; Li, Zhaoxi; Sun, Xinhao; Zheng, Chenxi; Yang, Yintang (Frontiers in Neuroscience, 2022)
Transcranial ultrasound stimulation (TUS) is a young neuromodulation technology, which uses ultrasound to achieve non-invasive stimulation or inhibition of deep intracranial brain regions, with the advantages of non-invasive, deep penetration, and high resolution. It is widely considered to be one of the most promising techniques for probing brain function and treating brain diseases. In preclinical studies, developing miniaturized transducers to facilitate neuromodulation in freely moving small animals is critical for understanding the mechanism and exploring potential applications. In this article, a miniaturized transducer with a half-concave structure is proposed. Based on the finite element simulation models established by PZFlex software, several ultrasound transducers with different concave curvatures were designed and analyzed. Based on the simulation results, half-concave focused ultrasonic transducers with curvature radii of 5 mm and 7.5 mm were fabricated. Additionally, the emission acoustic fields of the ultrasonic transducers with different structures were characterized at their thickness resonance frequencies of 1 MHz using a multifunctional ultrasonic test platform built in the laboratory. To verify the practical ability for neuromodulation, different ultrasound transducers were used to induce muscle activity in mice. As a result, the stimulation success rates were (32 ± 10)%, (65 ± 8)%, and (84 ± 7)%, respectively, by using flat, #7, and #5 transducers, which shows the simulation and experimental results have a good agreement and that the miniaturized half-concave transducer could effectively converge the acoustic energy and achieve precise and effective ultrasonic neuromodulation.